2007
DOI: 10.5704/moj.0705.006
|View full text |Cite
|
Sign up to set email alerts
|

Five Year Follow-up of One Stage Bilateral Total Hip Arthroplasty

Abstract: We report on the medium term outcome of five patients (ten hips) who underwent one stage bilateral total hip arthroplasty. Both Harris Hip Scores and Oxford Hip Scores improved postoperatively as did range of motion. There was no radiographic evidence of loosening in any hip arthroplasty involved in this study, however one revision surgery was needed due to periprosthetic fracture. There were no increased medical complications. Based on our limited experience, we believe that one stage bilateral total hip arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In 10 studies there was a pre-operative patients selection criterion for those submitted to bilateral one stage THR according to ASA grading [1,4,15,24,30,32,34,[40][41][42]. In 3 studies [1,34,41] high risk patients (ASA grades III and IV) were excluded, in 4 studies [15,30,32,40] only patients with grade IV were excluded, and in 3 studies [4,24,42] all grades (ASA grades I,II,III and IV) were included. In 6 studies an analysis of outcome according to ASA grading was reported [4,15,24,30,32,40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 10 studies there was a pre-operative patients selection criterion for those submitted to bilateral one stage THR according to ASA grading [1,4,15,24,30,32,34,[40][41][42]. In 3 studies [1,34,41] high risk patients (ASA grades III and IV) were excluded, in 4 studies [15,30,32,40] only patients with grade IV were excluded, and in 3 studies [4,24,42] all grades (ASA grades I,II,III and IV) were included. In 6 studies an analysis of outcome according to ASA grading was reported [4,15,24,30,32,40].…”
Section: Resultsmentioning
confidence: 99%
“…In most studies, grades 1 and 2 are considered as low risk and grades 3 and 4 as high risk for developing thromboembolic and cardiopulmonary complications. For that reason, patients with ASA grades 3 and 4 [41] or at least grade 4 [1,32,40] were excluded in studies with bilateral simultaneous THRs. Alfaro-Adrian et al [4] reported that ASA 3 and 4 grades had a higher incidence of DVT and PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation